1951
DOI: 10.1111/j.1151-2916.1951.tb13479.x
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Study and Equipment for Sintering and Testing of Cermet Bodies: V, Fabrication, Testing, and Properties of 30 Chromium–70 Alumina Cermets

Abstract: A cermet composition of 70y0 alumina-30% chromium has given very promising results as a new high-strength, refractory material. Bodies of the alumina-chromium composition with a particle size of 10 p and less were prepared and fabricated into test specimens under very closely controlled conditions of milling, pressing, and sintering. The fabricated specimens were tested in the laboratory, and results indicate that the material is extremely hard and resistant to oxidation and h a s outstanding strengths both at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1961
1961
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This is of some importance when the envelope is mechanically sealed on to the support. 40 Donovan 41 has described a refinement of the perforatedsupport concept in which a porous metal support is used against which the envelope can be expanded while being filled with powder. As noted earlier, control of shape is one of the major drawbacks to isostatic compaction and the accuracy that can be achieved is dependent upon the uniformity with which the powder is packed, as well as upon the provision of adequate support.…”
Section: Toolingmentioning
confidence: 99%
“…This is of some importance when the envelope is mechanically sealed on to the support. 40 Donovan 41 has described a refinement of the perforatedsupport concept in which a porous metal support is used against which the envelope can be expanded while being filled with powder. As noted earlier, control of shape is one of the major drawbacks to isostatic compaction and the accuracy that can be achieved is dependent upon the uniformity with which the powder is packed, as well as upon the provision of adequate support.…”
Section: Toolingmentioning
confidence: 99%
“…Multiple researches have shown that introducing small amounts of metal particles into the alumina matrix can significantly improve the mechanical properties of the ma-terial and thus increase its application potential. Presence of different metallic phases such as nickel [6][7][8], aluminium [9], iron [10], molybdenum [11,12], tungsten [13], chromium [14][15][16][17][18][19][20] or copper [21][22][23][24][25][26][27] and their influence on the properties of the obtained ceramic metal composites with alumina matrix has been the area of scientific interest in recent years. In all of the researches, incorporation of the metal particles into the alumina matrix has been proven to enhance a fracture toughness of the obtained composites.…”
Section: Introductionmentioning
confidence: 99%
“…Available research has proven that the addition of small amounts of copper into alumina ceramic matrix resulted in the improvement of the mechanical properties [21,26] and greater shock resistance of the composite material in comparison to the pure Al 2 O 3 ceramics [23]. Scientific literature in the case of Al 2 O 3 -Cr system indicates the possibility of use of the hot pressing [14,15], uniaxial pressing with pressureless sintering [14,18], combustion synthesis [19], mechanical and mechanical-thermal synthesis [17] or slip casting [20] as the efficient fabrication techniques. In all of the conducted studies, chromium addition to the alumina matrix caused enhancement of the mechanical properties of the material and its corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature on the subject, sintering Al 2 O 3 -Cr composites has been carried out so far at high temperatures. The first studies on sintering Al 2 O 3 -Cr composites were made by A.Blackburn and T.Shevlin [1], who used powder grains below 10µm, mixing them with an addition of methyl alcohol in ball mills over a period of 50 hours. The samples were sintered in the atmosphere of wet hydrogen under a high pressure (p=250MPa) at a temperature of 1700°C.…”
Section: Introductionmentioning
confidence: 99%